2010
DOI: 10.1021/jp909091s
|View full text |Cite
|
Sign up to set email alerts
|

Valence Band Structure and X-ray Spectra of Oxygen-Deficient Ferrites SrFeOx

Abstract: We present a study of the electronic structure of oxygen-deficient ferrites SrFeO x (x = 2.46, 2.52, 2.68, and 2.82) by means of X-ray photoelectron, X-ray emission, and X-ray absorption spectroscopies. From the Fe 3s photoelectron splitting, the magnetic moments are estimated. It is found that the doped holes are localized in both Fe 3d and O 2p states. The valence band structure is analyzed. It is shown that the band gap decreases with the increase of oxygen concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
54
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(69 citation statements)
references
References 39 publications
12
54
0
Order By: Relevance
“…In this thin film case, the oxygen-deficient layers can order parallel or perpendicular to the substrate (this is shown in Figure 3a and 3b, respectively, with the pseudocubic orientation shown in Figure 3c and 16,20,21 The indirect band gap of both compounds is approximately 2.0 eV, owing to a Γ-to X-point transition. 22 We find that, in agreement with experimental results of the bulk phases, the Pbcm and Pnma phase are the lowest energy (and thus equilibrium) structures for Sr 2 Fe 2 O 5…”
Section: Introductionsupporting
confidence: 88%
“…In this thin film case, the oxygen-deficient layers can order parallel or perpendicular to the substrate (this is shown in Figure 3a and 3b, respectively, with the pseudocubic orientation shown in Figure 3c and 16,20,21 The indirect band gap of both compounds is approximately 2.0 eV, owing to a Γ-to X-point transition. 22 We find that, in agreement with experimental results of the bulk phases, the Pbcm and Pnma phase are the lowest energy (and thus equilibrium) structures for Sr 2 Fe 2 O 5…”
Section: Introductionsupporting
confidence: 88%
“…This is expected if both CaFeO 3 and SrFeO 3 have the same formal Fe 4+ valence state because the optical parameters are derived from, and dominated by, the oxidation state‐dependent XA spectra (see Figure S3, Supporting Information), although the Bragg intensity is not fully suppressed due to the different non‐resonant contributions of Ca and Sr to the overall scattering factors. This supports the conclusion that the O ligand hole modulation is not due to oxygen vacancies, which would reduce the Fe valence and thus alter the Fe optical parameters . Second, rather than q 005 , the q 006 reflection exhibits behavior different from the other Bragg reflections.…”
supporting
confidence: 71%
“…The values of δ (i.e. the amount of oxygen vacancy) in SrFeO 3-δ were determined by comparing the X-ray adsorption spectra with previous references 33 , as shown in Figure S1 in the Supporting Information (SI). All oxides examined in this study were single phase, as revealed by X-ray diffraction (XRD), with lattice parameters listed in Table S1 in the SI.…”
Section: Oxides Synthesis and Bulk Characterizationmentioning
confidence: 99%